Climate change impacts on water resources and emerging strategies for sustainable management - Sivalinga Vijayan, Dhanasingh; Hangshing, Lamneithem; Sivasuriyan, Arvindan; Wodzyński, Łukasz Jan; Kiraga, Marta; Sitek, Wiktor; Koda, Eugeniusz (Journal of Water and Land Development, 2026)
The strong influence of climate change on terrestrial-aquatic ecosystems is illustrated by changes in the hydrological cycle, water quality degradation, and the intensification of extreme events such as floods and droughts. This review brings together the international evidence on the coupled impacts of climatic variability on freshwater availability, pollution, agricultural practices, and governance systems. The results suggest that changes in precipitation regimes, increases in ambient temperatures, and accelerated snowmelt all reduce streamflow and groundwater recharge. These alterations further disturb seasonal water availability, ecosystem services, and the long-term security of communities dependent on freshwater resources. At the same time, anthropogenic pollution and eutrophication are additional threats to aquatic ecosystems. Extreme climatic events increase the risk of flooding and drought, which in turn result in socio-economic losses and reduced agricultural productivity. Fisheries and food systems, more generally, are highly sensitive to increases in temperature and habitat degradation. The review also highlights that vulnerable regions require integrated monitoring, early-warning systems, and locally adaptable mitigation strategies. Good governance, grounded in the principles of equity, inclusion, and adaptive management, is needed for sustainable water allocation and resilience-building. The combination of climate-smart agricultural practices, technological interventions, and transboundary cooperation offers promising ways forward for achieving water sustainability amid future climatic uncertainty. Overall, the study emphasises the need for science-based policy, stakeholder participation, and coordinated international action.